PENGARUH UKURAN PERUSAHAAN, LEVERAGE, CAPITAL INTENSITY DAN PROFITABILITAS TERHADAP AGRESIVITAS PAJAK - Haloho , Flora Maida; Saragih, Afni Eliana (LPPM Universitas Katolik Santo Thomas Medan, 2023)
The aim of this research is to analyze the influence of company size, leverage, capital intensity and profitability on tax aggressiveness in food and beverage companies listed on the Indonesia Stock Exchange (BEI) in 2019-2021. The sampling technique was purposive sampling and 20 companies were determined to be the sample. Statistical tests found that the coefficient of determination (R square) was 0.211. This means that company size, leverage, capital intensity and profitability together influence tax aggressiveness, namely 21.1%. The research results found that company size and leverage had a positive and insignificant effect on tax aggressiveness. Capital intensity has a negative and insignificant effect on tax aggressiveness. Profitability has a negative and significant effect on tax aggressiveness.